Emotional Labor Actors: A Latent Profile Analysis of Emotional Labor Strategies - GABRIEL, Allison S. (Institutional Knowledge at Singapore Management University, 2015)
Research on emotional labor focuses on how employees utilize 2 main regulation strategies—surface acting (i.e., faking one’s felt emotions) and deep acting (i.e., attempting to feel required emotions)—to adhere to emotional expectations of their jobs. To date, researchers largely have considered how each strategy functions to predict outcomes in isolation. However, this variable-centered perspective ignores the possibility that there are subpopulations of employees who may differ in their combined use of surface and deep acting. To address this issue, we conducted 2 studies that examined surface acting and deep acting from a person-centered perspective. Using latent profile analysis, we identified 5 emotional labor profiles—non-actors, low actors, surface actors, deep actors, and regulators—and found that these actor profiles were distinguished by several emotional labor antecedents (positive affectivity, negative affectivity, display rules, customer orientation, and emotion demands–abilities fit) and differentially predicted employee outcomes (emotional exhaustion, job satisfaction, and felt inauthenticity). Our results reveal new insights into the nature of emotion regulation in emotional labor contexts and how different employees may characteristically use distinct combinations of emotion regulation strategies to manage their emotional expressions at work.